Set theory versus Neo-Riemannian Theory: Two interdependent approaches in the analysis of choros # 4 and # 7 of Villa-Lobos (Revista da Tulha, 2015)
This paper proposes a simultaneous parallel between two different parameters of musical analysis which in our study appeared interdependent and necessary for building a sufficient theoretical framework for an understanding of the compositional aesthetic profile applied by Villa-Lobos in the classes of pitches in two excerpts of works from the 1920s: Choros # 4 and # 7.